Smart Campus Applications: A Literature Review on Operations Research and Big Data - Ivan Kristianto Singgih; Aditya Rio Prabowo; Stefanus Soegiharto; Moses Laksono Singgih; Fajar Pitarsi Dharma (International Journal of Technology)
Industry 4.0-related technologies are being implemented to improve societal well-being, and smart campus is a significant application area. Smart campus integrates various technologies for online class management, energy usage observation, warning systems, smart vehicles, and people flow management. Therefore, this study aimed to list and classify surveys on smart campus applications. Unlike previous reviews, a broad range of topics, and characteristics of smart campus applications were explored. A total of 43 studies were identified and screened using Google Scholar database according to the PRISMA framework. An overview of each application topic was provided, detailing its functions, related data, and technologies used. In addition, transportation problems related to these applications were identified, offering areas for future studies to optimize smart campus systems.